Meandering tidal-fluvial channels and lag concentration of terrestrial vertebrates in the fluvial- tidal transition of an ancient estuary in Patagonia. - Roberto A. Scasso; María Teresa Dozo; José I. Cuitiño; Pablo Bouza (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The La Pastosa beds constitute a nice example of sediments deposited in the highly meandering reach of the fluvial-tidal transition within an estuary, developed at the top of the “Rionegrense” stage, a marine-estuarine sequence of late Miocene age from Patagonia. Sedimentary facies include channel lags rich in mud intraclasts; cross-bedded sandstones with mud drapes and “set-climber” ripples; heterolithic and herringbone bedding; and inclined heterolithic stratification (IHS), and suggest a strong tidal influence. Tidal facies together with paucity of bioturbation and marine fossils indicate that sedimentation took place mainly in brackish tidal-fluvial channels, bounded by deposits formed in transgressive conditions at the base and at the top of the succession. Channel lag intraformational conglomerates are product of collapse of the cutbank due to erosion in the active margin of lateral migrating meandering channels that eroded adjacent muddy tidal flats and salt marshes. Cross- bedded sandstones were accumulated above the conglomerates, forming subtidal sand dunes in the deeper parts of the channels and IHS was formed in point bars. Discontinuities at the base of the channels are the result of the entire channel-system lateral migration, whereas discontinuities capped by small mud pebbles at the base of large IHS sets are the result of seasonally increased run-off and widening of the channels. Alternation of sandy and muddy IHS suggests periodical changes in the position of the turbidity maximum due to seasonal variation of fluvial discharge, in good agreement with the seasonal climate in Patagonia during the late Miocene. IHS sets dipping alternatively to the north and south indicate lateral migration of the east-west running, high-sinuosity channels in the tightly meandering reach of the tidal-fluvial transition. The well preserved vertebrate fauna of Huayquerian mammal age is dominated by the hydrocherid Cardiatherium patagonicum together with whistling ducks and loricariid fishes. This fauna inhabited out-of-channel, freshwater, low-energy restricted environments, like marshes and ponds where the carcasses accumulated and underwent diagenetic fossilization. Repeated lateral migration of meandering channels caused erosion of these deposits and the bones were exhumed and incorporated into the channels, and finally concentrated in channel lags after short transport. Combination of fossilization in a low-energy environment and concentration after short transport in meandering channels make the fluvial-tidal transition “first class” deposits for prospecting vertebrate fossils. In spite of exhumation and transport, vertebrate fossil association closely reflects the environments adjacent to the channels. Excellent preservation is more related to rapid burial than to the energy level of the environment of final accumulation.